Building winners? An empirical evaluation of public business assistance in the founding process - Sarah Kösters; Martin Obschonka (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
This paper investigates economic and subjective effects of public business assistance delivered to nascent entrepreneurs in Germany. Employing cluster analysis, we explore the actual scope and intensity of business assistance used. Then we analyze predictors of take-up and perceived usefulness taking into account the different patterns of utilized assistance. Finally, we assess economic effects by studying subsequent business performance employing propensity score matching. We cannot reveal that business assistance translates into better start-up performance. However, we find that a lack of personal entrepreneurial resources predicts take-up of business assistance in general as well as perceived usefulness of comprehensive business assistance.
Keywords: O38; L26; H59; 330; entrepreneurship; business assistance; policy evaluation; entrepreneurial resources; big five; Unternehmensgründung; Unternehmer; Wirtschaftsförderung; Wirkungsanalyse; Unternehmensentwicklung; Deutschland